Optimization of photocatalytic fuel cells (PFCs) in the treatment of diluted palm oil mill effluent (POME) - Nur Syahidda Ani, Moksin; Ong, Yong Por; Ho, Li Ngee; Tay, Meng Guan (Elsevier, 2021)
Photocatalytic fuel cells (PFCs) are considered an advanced technology in wastewater treatment as they are able to remove organic based wastewater by using the principle of advanced oxidation processes (AOPs) and at the same time generate electricity. Despite PFCs being used to treat different types of organic based wastewater efficiently, the use of PFCs in palm oil mill effluent (POME) is still considered rare. Hence, the present research was carried out to determine the optimal conditions of contact time, pH, initial organic concentration and light intensity in order to remove the organic matter present in diluted POME. Our PFC system was constructed by using NaCl as the supporting electrolyte with ZnO/Zn as the photoanode and platinum wire as the cathode. The chemical oxygen demand (COD) removal efficiency and the amount of electricity generated was monitored in different optimization experiments using a conventional fluorescence light source. Under optimal conditions, the COD removal efficiency increased from 7% to 74 %, while the power density output also increased from 1.73 to 35.85 μW/cm2. The PFC was found to work optimally at pH 7 with a light intensity of 1300 lx for 6 h. Meanwhile, the scanning electron microscope (SEM) images revealed the high organic matter concentration in POME can lead to the deposition of an organic layer on the photoanode surface which subsequently reduced the COD removal efficiency to 17.4 %. This result has indicated that PFC is not suitable for treating the fresh POME directly from the mill, but it is more suitable for treating POME, from the last biological treatment pond.